2011
DOI: 10.1159/000335364
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Survival between Patients with Dementia with Lewy Bodies and Patients with Alzheimer's Disease - Measured from a Fixed Cognitive Level

Abstract: Introduction: The aim of this study was to compare survival in patients with Alzheimer's disease (AD) and patients with dementia with Lewy bodies (DLB). Since anamnestic and retrospective information about disease duration are unreliable variables, we measured survival from a fixed cognitive level. Methods: Survival time was measured from the reported disease onset, from the time of diagnosis, from Mini-Mental State Examination (MMSE) 20 ± 1, and from MMSE 17 ± 1. Results: Survival time was significantly short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 79 publications
5
29
1
1
Order By: Relevance
“…They support and extend the results of a previous study reporting that the difference in mortality between AD and DLB increases with an MMSE score of approximately 20 [28]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They support and extend the results of a previous study reporting that the difference in mortality between AD and DLB increases with an MMSE score of approximately 20 [28]. …”
Section: Discussionsupporting
confidence: 90%
“…Also in line with previous studies, we identified age at baseline and a diagnosis of LBD as predicting factors of mortality [7,28]. The univariable analysis also showed significant results for comorbidity and disease severity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies have defined survival in two ways, either from onset of disease, or from diagnosis. Survival estimates range between 5.5 and 7.7 years, and between 1.9 and 6.3 years respectively for these two definitions 22,27,32,[44][45][46] . To mitigate potential inaccuracies due to recall bias of duration and delay in diagnosis, Stubendorff and colleagues 45 measured survival from fixed MMSE score points (20±1 and 17±1), demonstrating worse survival in DLB than in AD patients.…”
Section: Longevity and Mortalitymentioning
confidence: 98%
“…Other comparison studies evaluating survival differences in patients with AD and DLB have found that when comparing the groups based on Mini-Mental State Examination score, the survival time is shorter in DLB [38]. The evidence suggests that DLB patients may have worse mortality outcomes; however, the rate of cognitive decline over time is similar between DLB and AD patients [36].…”
Section: Impact Of Disease On Family Caregiversmentioning
confidence: 99%